2021
DOI: 10.1007/s00531-021-02038-4
|View full text |Cite
|
Sign up to set email alerts
|

Polyphase extensional basins: interplay between tectonics and sedimentation in the Neogene Siena-Radicofani Basin (Northern Apennines, Italy)

Abstract: Rift-basins are the shallow effects of lithosphere-scale extensional processes often producing polyphase faulting. Their sedimentary evolution depends on the mutual interplay between tectonics, climate, and eustasy. Estimating the role of each factor is generally a challenging issue. This paper is focused on the tectono-sedimentary evolution of the Neogene Siena-Radicofani Basin, a polyphase structural depression located in the inner Northern Apennines. Since Miocene, this basin developed after prolonged exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…3B) is part of the Siena-Radicofani Basin, a NNW-SSE structural depression of 90 km, developed during Neogene extensional activity. The basin is filled by Pliocene marine deposits, overlain by Quaternary continental succession mainly composed by gravel, sand, clay and travertine deposits (Bertini et al, 1991;Bossio et al, 1993;Martini and Sagri, 1993;Carmignani et al, 1994;Liotta et al, 1998;Costantini et al, 2009;Lazzarotto et al, 2010;Ghinassi et al, 2021;Martini et al, 2021). The travertine deposits (Pleistocene-Holocene) develop on an area of 14 km 2 with a thickness of approximatively 50 m (Brogi, 2004).…”
Section: Geological Setting Of the Rapolano Terme Areamentioning
confidence: 99%
“…3B) is part of the Siena-Radicofani Basin, a NNW-SSE structural depression of 90 km, developed during Neogene extensional activity. The basin is filled by Pliocene marine deposits, overlain by Quaternary continental succession mainly composed by gravel, sand, clay and travertine deposits (Bertini et al, 1991;Bossio et al, 1993;Martini and Sagri, 1993;Carmignani et al, 1994;Liotta et al, 1998;Costantini et al, 2009;Lazzarotto et al, 2010;Ghinassi et al, 2021;Martini et al, 2021). The travertine deposits (Pleistocene-Holocene) develop on an area of 14 km 2 with a thickness of approximatively 50 m (Brogi, 2004).…”
Section: Geological Setting Of the Rapolano Terme Areamentioning
confidence: 99%
“…Beginning in early Miocene time, the previously stacked units were affected by extension (Carmignani et al 2001). Extension produced: (a) lateral segmentation of the previously stacked units and formation of bowl-shaped basins (Brogi & Liotta, 2008; Brogi, 2011); and (b) development of NW-striking Pliocene–Quaternary normal faults, cross-cutting all the previous structures and inducing development of NW-trending tectonic depressions, filled by continental and marine sediments (Martini & Sagri, 1993; Brogi et al 2013; Martini et al 2021). The primary evidence of extension is the opening of the Tyrrhenian Basin (Bartole, 1995) and the present crustal and lithospheric thicknesses of ∼17 and 40 km, respectively (Calcagnile & Panza, 1981; Locardi & Nicolich, 1982; Di Stefano et al 2011; Möller et al 2013).…”
Section: Geological Outlinementioning
confidence: 99%
“…The investigated sedimentary succession (Figure 3) is part of the sedimentary fill of the Middle Ombrone Basin of Tuscany ( [17][18][19]; cf. with the Cinigiano-Baccinello Basin of [20]), one of several continental to marine Plio-Quaternary basins (Figure 1a) formed since the late Neogene as a result of crustal extension in the Apennine hinterland [17,[21][22][23][24][25]. These late orogenic basins are regarded as graben-like elongated depocentres striking parallel to the central Apennine chain that were infilled relatively rapidly by continental and shallow marine clastics [23,26].…”
Section: Geological Settingmentioning
confidence: 99%
“…Even though a purely extensional horst-and-graben model is supported by the lack of significant tectonic rotation since the late Messinian [27], other authors suggested that late orogenic basins of Tuscany may have formed in a more complex tectonic setting, in which compressional, extensional and strike-slip stress regimes coexisted and/or alternated over time [28,29]. Recently, other studies suggested that these basins developed as hanging-wall basins associated with extensional detachments (Serravallianlate Messinian) that formed a bowl-shaped structural depressions later dissected by late Zanclean-early Piacenzian high-angle normal faults [25,30,31]. [20] and [32]) with location of the sections making the Brunella composite section; (c) stratigraphic log of the Brunella composite section with positions of samples.…”
Section: Geological Settingmentioning
confidence: 99%